2018
DOI: 10.1089/jop.2017.0041
|View full text |Cite
|
Sign up to set email alerts
|

Targets of Neuroprotection in Glaucoma

Abstract: Progressive neurodegeneration of the optic nerve and the loss of retinal ganglion cells is a hallmark of glaucoma, the leading cause of irreversible blindness worldwide, with primary open-angle glaucoma (POAG) being the most frequent form of glaucoma in the Western world. While some genetic mutations have been identified for some glaucomas, those associated with POAG are limited and for most POAG patients, the etiology is still unclear. Unfortunately, treatment of this neurodegenerative disease and other retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 263 publications
2
76
0
6
Order By: Relevance
“…Furthermore, Wang et al have reported that laminin α4 (LAMA4) is involved in the development of glaucoma and that downregulation of LAMA4 might reduce ROS-induced apoptosis of RGCs by inhibiting the activation of the MAPK signaling pathway [ 222 ]. In another study, neurotrophins (NTs) were shown to be promising agents for neuroprotection activated by NT signaling through Trk receptors by the PI3-K-Akt-TOR and the MEK/ERK1/2/MAP kinase pathways, evoking protective and cell survival responses in the retina [ 223 ]. A small-molecule inhibitor (tozasertib) was shown to inhibit the JNK pathway and to promote RGC survival in an in vivo rodent optic nerve transection model [ 223 , 224 ].…”
Section: Therapeutic Strategies To Reduce Oxidative Stressmentioning
confidence: 99%
“…Furthermore, Wang et al have reported that laminin α4 (LAMA4) is involved in the development of glaucoma and that downregulation of LAMA4 might reduce ROS-induced apoptosis of RGCs by inhibiting the activation of the MAPK signaling pathway [ 222 ]. In another study, neurotrophins (NTs) were shown to be promising agents for neuroprotection activated by NT signaling through Trk receptors by the PI3-K-Akt-TOR and the MEK/ERK1/2/MAP kinase pathways, evoking protective and cell survival responses in the retina [ 223 ]. A small-molecule inhibitor (tozasertib) was shown to inhibit the JNK pathway and to promote RGC survival in an in vivo rodent optic nerve transection model [ 223 , 224 ].…”
Section: Therapeutic Strategies To Reduce Oxidative Stressmentioning
confidence: 99%
“…In glaucoma, neuroprotection has been defined as an intervention independent of IOP reduction that prevents retinal ganglion cell (RGC) death. Neurotrophins, including ciliary-derived neurotrophic factor (CNTF), brain-derived neurotrophic factor (BDNF), glial-derived neurotrophic factor (GNTF), and nerve growth factor (NGF), are promising agents in neuroprotection in glaucoma [78]. These factors are thought to reduce the loss of RGCs by arresting the apoptotic pathway or inhibiting intracellular death signals.…”
Section: Future Directionmentioning
confidence: 99%
“…These factors are thought to reduce the loss of RGCs by arresting the apoptotic pathway or inhibiting intracellular death signals. Active research is focused on isolating which factors have effects in the RGCs and how to get them secreted into the correct location [78][79][80][81]. However, as of yet, no agents have been able to demonstrate a clear neuroprotective effect.…”
Section: Future Directionmentioning
confidence: 99%
“…Op het vlak van neuroprotectieve agentia werd er in de humane geneeskunde reeds heel wat onderzoek verricht (Corredor en Goldberg, 2009;Hegde et al, 2010;Hare et al, 2011;Chang en Goldberg, 2012;Chrysostomou et al, 2013;Yu et al, 2013;Cislo-Pakuluk en Marycz, 2017). Hoewel de toekomstperspectieven voor glaucoomtherapie bij honden er veelbelovend uitzien (Adams et al, 2018), moeten op het vlak van neuroprotectie talrijke uitdagingen worden aangegaan, inclusief de ontwikkeling van adequate diermodellen equivalent aan de humane tegenhanger (He et al, 2017). Dankzij laboratoriumonderzoek wordt de kennis van de factoren die bijdragen tot de pathogenese continu op peil gesteld, wat uiteindelijk kan leiden tot de ontwikkeling van verbeterde neuroprotectieve strategieën en de klinische toepassing ervan (Adams et al, 2018).…”
Section: Neuroprotectie En Neurodegenera-tieunclassified